Eckhartian Mysticism as Scholastic Humanism. Issue 1 (2nd January 2019) - Dobie, Robert J.
ABSTRACT: This essay seeks to propose a new way of looking at the so-called mysticism of Meister Eckhart as a 'scholastic humanism' Eckhart's thought is "humanist" in the sense that it argues that all truth is such only insofar as it is appropriated by and transforms intellectually and existentially the individually existing human being; but Eckhart's humanism is scholastic insofar as it sees the truths of scholastic philosophy and theology as being firmly rooted in this lived and inner appropriation of truth. To this end, this essay explores the ways in which Eckhart "translates" the often static and abstract categories of Aristotelian-Scholastic theology into what he argues is their lived, inner origin in the soul's journey to union with God. And what makes this appropriation of truth by the individual human being possible is that the inner "ground" of the human existence is also the inner "ground" of God, the principle of all existence, an identity revealed and actualized in the incarnation of Jesus Christ. Thus, Eckhart's "scholastic humanism" is also a thoroughly Christian humanism.